2019
DOI: 10.1186/s13059-019-1825-x
|View full text |Cite
|
Sign up to set email alerts
|

Soil domestication by rice cultivation results in plant-soil feedback through shifts in soil microbiota

Abstract: BackgroundSoils are a key component of agricultural productivity, and soil microbiota determine the availability of many essential plant nutrients. Agricultural domestication of soils, that is, the conversion of previously uncultivated soils to a cultivated state, is frequently accompanied by intensive monoculture, especially in the developing world. However, there is limited understanding of how continuous cultivation alters the structure of prokaryotic soil microbiota after soil domestication, including to w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
47
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 72 publications
(54 citation statements)
references
References 55 publications
6
47
0
1
Order By: Relevance
“…However, the effect of root exudates on rhizobiome assembly is complicated, and the strategy of rootassociated microbial community assembly at the soil-root interface remains controversial. The findings of some studies on root-associated microbiota in rice corroborate a two-step or multiple-step model in the root microbiota assembly, where specific microbial taxa in soil gradually become depleted or enriched during root colonization 15,22 . Other studies on rice and Medicago root-associated microbiota pointed to the applicability of the amplification-selection process, where dominant phyla would undergo substantial enrichment in the rhizosphere followed by the specific recruitment of certain phyla into the roots 23 .…”
Section: Introductionmentioning
confidence: 59%
“…However, the effect of root exudates on rhizobiome assembly is complicated, and the strategy of rootassociated microbial community assembly at the soil-root interface remains controversial. The findings of some studies on root-associated microbiota in rice corroborate a two-step or multiple-step model in the root microbiota assembly, where specific microbial taxa in soil gradually become depleted or enriched during root colonization 15,22 . Other studies on rice and Medicago root-associated microbiota pointed to the applicability of the amplification-selection process, where dominant phyla would undergo substantial enrichment in the rhizosphere followed by the specific recruitment of certain phyla into the roots 23 .…”
Section: Introductionmentioning
confidence: 59%
“…Rice ( Oryza sativa L.) exists as two ecotypes, upland and irrigated ecotypes, which are adapted to rainfed upland conditions and well-watered conditions, respectively [ 40 , 41 ]. However, previous studies on the rice microbiome or PGPR have focused mainly on irrigated rice [ 11 , 42 , 43 , 44 , 45 , 46 , 47 , 48 ]. Recent studies have proven that there may be great differences between root microbes of irrigated rice and drought-stressed rice [ 10 , 49 , 50 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, a study has recently shown that Methanobacterium OTUs were more enriched in the endosphere of rice plants than in other native plant species growing in the same field, indicating that Methanobacterium spp. have a unique interaction with rice (45). Previous studies have correlated the activity of superoxide dismutase with oxygen tolerance in some taxa, including Methanobacterium, as well as some anaerobic taxa discussed above (e.g., Desulfovibrio and Propionivibrio) (46)(47)(48).…”
Section: Discussionmentioning
confidence: 99%